Dynamics of Ultrathin Vanadium Oxide Layers on Rh(111) and Rh(110) Surfaces During Catalytic Reactions - von Boehn, Bernhard; Imbihl, Ronald (Frontiers in Chemistry, 2020)
Over the past 35 years rate oscillations and chemical wave patterns have been extensively studied on metal surfaces, while little is known about the dynamics of catalytic oxide surfaces under reaction conditions. Here we report on the behavior of ultrathin V oxide layers epitaxially grown on Rh(111) and Rh(110) single crystal surfaces during catalytic methanol oxidation. We use photoemission electron microscopy and low-energy electron microscopy to study the surface dynamics in the 10-6 to 10-2 mbar range. On VOx/Rh(111) we find a ripening mechanism in which VOx islands of macroscopic size move towards each other and coalesce under reaction conditions. A polymerization/depolymerization mechanism of VOx that is sensitive to gradients in the oxygen coverage explains this behavior. The existence of a substructure in VOx islands gives rise to an instability, in which a VOx island shrinks and expands in an oscillatory manner around a critical radius. At 10-2 mbar the VOx islands are no longer stable but they disintegrate, leading to turbulent redistribution dynamics of VOx. On the more open and thermodynamically less stable Rh(110) surface the behavior of VOx is much more complex than on Rh(111), as V can also populate subsurface sites. At low V coverage, one finds traveling interface pulses in the bistable range. A state-dependent anisotropy of the surface is presumably responsible for intriguing chemical wave patterns: wave fragments traveling along certain crystallographic directions, and coexisting different front geometries in the range of dynamic bistability. Annealing to 1000 K causes the formation of macroscopic VOx islands. Under more reducing conditions dendritic growth of a VOx overlayer is observed.